2019
DOI: 10.3390/polym11081261
|View full text |Cite
|
Sign up to set email alerts
|

Strong Interaction with Carbon Filler of Polymers Obtained by Pyrene Functionalized Hoveyda-Grubbs 2nd Generation Catalyst

Abstract: Hoveyda-Grubbs 2nd generation catalyst that has the alkylidene functionalized with pyrene (HG2pyrene) was synthesized and characterized. This catalyst can be bound to carbonaceous filler (graphite, graphene or carbon nanotubes) by π-stacking interaction, but, since the catalytic site become poorly accessible to the incoming monomer, its activity in the ROMP (Ring Opening Metathesis Polymerization) is reduced. This is due to the fact that the above interaction also occurs with the aryl groups of NHC ligand of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Solid polymer electrolytes intercalate into graphite oxide due to the dipole–dipole and/or hydrogen bonding forces of attraction between the polymers and graphene oxide . A computational study on the interaction between pristine graphene and graphene oxide and several polymers found that the lowest energy conformer of the β-conformation of polyvinylidene fluoride with the hydrogen atoms facing the graphene had the strongest interaction. …”
Section: Resultsmentioning
confidence: 99%
“…Solid polymer electrolytes intercalate into graphite oxide due to the dipole–dipole and/or hydrogen bonding forces of attraction between the polymers and graphene oxide . A computational study on the interaction between pristine graphene and graphene oxide and several polymers found that the lowest energy conformer of the β-conformation of polyvinylidene fluoride with the hydrogen atoms facing the graphene had the strongest interaction. …”
Section: Resultsmentioning
confidence: 99%